Digital Dental Photography-A Modern Revolution - M.A.Eswaran; G.Priya; A.Brighton Maniselvan; A.Vishwani; Tanaaz Khan; R.Karthika (Indian Journal of Forensic Medicine & Toxicology, 2021)
Digital photography has multilevel significance and represents the synonym of contemporary dentistry. Itsapplication in dental practice is simple, fast, and extremely useful in documenting procedures of work,effectuating the education of patients, and pursuing clinical investigations, thus providing many dentists andpatient. This article aims to review the various features and advancements in the field of dental photographyand its application in prosthodontics.